PROFILE OF ELDERLY PEOPLE WHO NEEDED DENTURE AT WAJO REGENCY: PROFIL MASYARAKAT LANJUT USIA YANG MEMBUTUHKAN GIGI TIRUAN DI KABUPATEN WAJO - Edy Machmud (Dentika: Dental Journal, 2010)
The main problem faced by the elderly people is tooth loss. A number of tooth loss will affect a health in general,as it will disrupt mastication process and finally will cause malnutrition and gastritis. Therefore, teeth should besubstituted with dentures. The aim of this study was to have a picture of elderly people profile who needed adenture teatment at Wajo regency, South Sulawesi province. A research method by purposive random samplingof 703 samples of elderly people with age equal or above 55 years old by fulfilling a questioner. The result ofthis study showed that all of 703 samples had tooth loss, 29,26% with 1-10 tooth loss, 28,0% with 11-20 toothloss, more than 20 teeth (42.1%), and edentulous 0,7%. Only 1 % of the samples used denture. In conclusion,knowledge of community related oral and dental health and the importance of substituting tooth loss withdenture is very limited or low.